2020
DOI: 10.1017/s1047951120000189
|View full text |Cite
|
Sign up to set email alerts
|

Sinus Superflex DS© early collapse in systemic arterial duct

Abstract: We implanted two sinus Superflex DS© stents in a systemic non-stenotic arterial duct of a newborn with hypoplastic left heart syndrome. Forty-eight hours later an important collapse of the stent was detected and treated with a balloon expandable stent. Sinus Superflex DS© has been specifically designed for systemic ducts. This complication generates doubts about its radial force in this scenario.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…4 Early reports suggested that SSF exerted enough radial force to maintain ductal patency in constricted ducts, with a minority of cases requiring balloon dilatation of residual narrowings (two of 22 cases). 4 Betrian-Blasco et al 6 reports two cases of early SSF collapse within 48 h of the procedure after stenting a non-stenosing neonatal duct for HLHS that required re-stenting with a balloon expandable stent.…”
Section: Discussionmentioning
confidence: 99%
“…4 Early reports suggested that SSF exerted enough radial force to maintain ductal patency in constricted ducts, with a minority of cases requiring balloon dilatation of residual narrowings (two of 22 cases). 4 Betrian-Blasco et al 6 reports two cases of early SSF collapse within 48 h of the procedure after stenting a non-stenosing neonatal duct for HLHS that required re-stenting with a balloon expandable stent.…”
Section: Discussionmentioning
confidence: 99%
“…The former is characterized by an open-cell design to provide an effective combination between conformability and radial force, with diameters ranging from 4 mm to 9 mm; the latter has a closed-cell design and is indicated for combined treatment of aortic coarctation, with size of 5 mm and 6 mm. However, controversial outcomes have been reported: while some studies reveal positive follow-up with sufficient radial strength, good hemodynamics, and reduced wall trauma [77,78], others report early collapse due to insufficient radial force and severe restenosis [73,76].…”
Section: Pulmonary Atresiamentioning
confidence: 99%
“…stent (C)[68,71,72] Omnilink (O)[68,72] Saxx stent (C)[68,71,72] Precise (O)[74] Protégé (O)[70,74,75] Sinus-Repo-DS (C)[68] Sinus-SuperFlex-DS (O)[73,[76][77][78] Sinus-SuperFlex-DS (O)[73,[76][77][78] Appl. Sci.…”
mentioning
confidence: 99%